Advantages, Challenges, and Future Directions of Communicative Language Teaching: A Systematic Literature Review (2021-2025) - Flores, Clyde Konrad; Villar, Gladys Kaye; Abad, Rashmin Clem; Liwas, Mickey Mie; Pelila, John Rey (Papanda Publisher, 2026)
Communicative Language Teaching (CLT) is widely used to promote meaningful communication in English classrooms, yet its implementation remains inconsistent across educational contexts. Despite its global adoption, teachers continue to face pedagogical and systemic challenges that limit the full use of communicative practices. This study reviews and synthesizes the advantages, disadvantages, and recommendations reported in 25 peer-reviewed studies published between 2021 and 2025. Using a Systematic Literature Review (SLR) guided by PRISMA 2020, 327 records were screened and thematically analyzed. Findings indicate that CLT effectively enhances students’ communicative competence by increasing interaction, engagement, and confidence through collaborative and task-based activities. However, major challenges remain, including insufficient teacher training, low learner confidence, large class sizes, exam-driven instruction, and mismatches between CLT principles and local educational cultures. Recommendations across studies emphasize strengthening teacher professional development, adapting CLT to local contexts, and integrating technology to support communicative tasks. The review concludes that while CLT is a flexible and effective approach, its success depends on contextual adaptation, institutional support, and sustained teacher preparedness. Strengthening training programs and developing culturally responsive, technology-supported CLT models are highly recommended to achieve meaningful and consistent outcomes in diverse learning environments.